2020
DOI: 10.3390/antiox9020106
|View full text |Cite
|
Sign up to set email alerts
|

Maslinic Acid Ameliorates Inflammation via the Downregulation of NF-κB and STAT-1

Abstract: Maslinic acid (MA), a natural compound of the triterpenoid group derived from olive, prevents the generation of pro-inflammatory cytokines and oxidative stress. In human umbilical vein endothelial cells (HUVECs) treated with lipopolysaccharide (LPS), we characterized the effects of MA on the regulation of heme oxygenase (HO)-1, cyclooxygenase (COX-)2, and inducible nitric oxide synthase (iNOS). MA was tested in the lung tissues of LPS-treated mice, to determine its effect on levels of iNOS expression and repre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
35
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(37 citation statements)
references
References 25 publications
2
35
0
Order By: Relevance
“…Additionally, Ampofo et al [ 92 ] described a maslinic acid-dependent downregulation of NF-κB in endothelial cells, paralleled by increased eNOS expression and reduced oxidative DNA damage. Experiments carried out in human umbilical vein endothelial cells (HUVEC) also demonstrated NF-κB downregulation by maslinic acid [ 93 ]. Furthermore, ursolic and oleanolic acids have also been described as promising anti-inflammatory compounds via NF-κB inactivation [ 94 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, Ampofo et al [ 92 ] described a maslinic acid-dependent downregulation of NF-κB in endothelial cells, paralleled by increased eNOS expression and reduced oxidative DNA damage. Experiments carried out in human umbilical vein endothelial cells (HUVEC) also demonstrated NF-κB downregulation by maslinic acid [ 93 ]. Furthermore, ursolic and oleanolic acids have also been described as promising anti-inflammatory compounds via NF-κB inactivation [ 94 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several authors have attributed to OO the ability to modulate Nrf-2 [ 99 ], where polyphenols such as secoiridoids seem to be positively implicated in this effect [ 62 ], as these are also associated with a reduction in NF-κB levels [ 100 ]. In the same way, maslinic [ 93 ] and ursolic acids [ 101 ] are also positive modulators of Nrf-2 with beneficial effects against oxidative/inflammatory damage in different situations.…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, ursolic acid in combination with leucine can stimulate myoblast differentiation and muscle mass increase through the induction of the mTOR pathway [ 278 ]. In addition, triterpenoid compounds exert anti-inflammatory action inhibiting NF-κB, COX-2, iNOS, TNF-α [ 260 , 289 , 290 , 291 , 292 , 293 , 294 , 295 ].…”
Section: Terpenoids As Potential Geroprotectorsmentioning
confidence: 99%
“…In addition, oleanolic acid has bone anti-resorption activity in aged female rats and can be applied in osteoporosis prevention [ 330 ]. Due to anti-inflammatory activity, triterpenoids, such as maslinic acid, can prevent related diseases, particularly arthritis [ 294 , 295 ]. Squalene and ginsenosides can be used for the protection against skin photoaging [ 242 , 273 ].…”
Section: Terpenoids As Potential Geroprotectorsmentioning
confidence: 99%
“…Recent studies suggest that maslinic acid inhibits PI3K/AKT signaling in human aortic endothelial cells (F. Li, Li, Shi, & Guo, 2017). It has also been reported that maslinic acid exerts anti-inflammatory effect by downregulating NF-κB (Lee, Kim, Park, & Bae, 2020). Although the anti-inflammatory effects of MA have been extensively studied, the mechanism of regulation of inflammatory cells in OA remains unclear.…”
Section: Introductionmentioning
confidence: 99%